1999
DOI: 10.1094/mpmi.1999.12.2.129
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Pathogenicity Mutants of the Rice Blast Fungus Magnaporthe grisea by Insertional Mutagenesis

Abstract: Restriction enzyme-mediated DNA integration (REMI) mutagenesis was used to identify mutants of Magnaporthe grisea impaired in pathogenicity. Three REMI protocols were evaluated and the frequency of REMIs determined. An REMI library of 3,527 M. grisea transformants was generated in three genetic backgrounds, and 1,150 transformants were screened for defects in pathogenicity with a barley cut leaf assay. Five mutants were identified and characterized. Two mutants (2029 and 2050) were impaired in appressorium fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
97
0
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 145 publications
(102 citation statements)
references
References 57 publications
2
97
0
3
Order By: Relevance
“…This, in turn, triggers multiple mitogen-activated protein kinase cascades, resulting in differentiation of the appressorium, transport of lipid and carbohydrate reserves to the infection cell, and generation of appressorial turgor (Mitchell and Dean, 1995; Xu and Hamer, 1996;Choi and Dean, 1997;Liu and Dean, 1997; Xu et al, 1997 Xu et al, , 1998Adachi and Hamer, 1998;Dixon et al, 1999; Thines et al, 2000). How appressorium development culminates in plant infection, however, is less clear because the genetic components required for penetration peg formation have not yet been identified.Our aim in this study was to identify and characterize the PDE1 gene, which had been defined previously by identification of an insertional mutant impaired in plant infection (Balhadère et al, 1999). When we analyzed the plant infection process in pde1 mutants at the ultrastructural level, we found that cuticle penetration was reduced dramatically, and the only penetration structures observed were nonpolarized hyphae that were limited to the initial epidermal cell.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…This, in turn, triggers multiple mitogen-activated protein kinase cascades, resulting in differentiation of the appressorium, transport of lipid and carbohydrate reserves to the infection cell, and generation of appressorial turgor (Mitchell and Dean, 1995; Xu and Hamer, 1996;Choi and Dean, 1997;Liu and Dean, 1997; Xu et al, 1997 Xu et al, , 1998Adachi and Hamer, 1998;Dixon et al, 1999; Thines et al, 2000). How appressorium development culminates in plant infection, however, is less clear because the genetic components required for penetration peg formation have not yet been identified.Our aim in this study was to identify and characterize the PDE1 gene, which had been defined previously by identification of an insertional mutant impaired in plant infection (Balhadère et al, 1999). When we analyzed the plant infection process in pde1 mutants at the ultrastructural level, we found that cuticle penetration was reduced dramatically, and the only penetration structures observed were nonpolarized hyphae that were limited to the initial epidermal cell.…”
mentioning
confidence: 95%
“…Among the mutants we identified was a penetration-defective mutant called pde1 . The pde1 mutant exhibited reduced appressorium-mediated penetration and produced very few disease symptoms when inoculated onto a susceptible plant host (Balhadère et al, 1999). In this article, we report that PDE1 encodes a P-type ATPase belonging to a family of aminophospholipid translocases.…”
mentioning
confidence: 98%
“…Although the enzyme type and concentration have an important impact on the number of transformants and the frequency of single-copy integrations, there are no clear rules for selecting either [56,64,66], and the npg concentration of RE that produces the maximum number of transformants is enzyme and host dependent [66][67][68]. REMI can give rise to a significant number of different integration events including single insertion with deletion of flanking RE sites, ectopic integration in the absence of an appropriate RE site, tandem insertion and large genome deletions or inversions [50,56,64,65,68,69]. The high frequency with which the mutant phenotype is not linked to the integrated DNA greatly complicates the use of this system for gene discovery.…”
Section: Gene Tagging By Direct Dna Transfermentioning
confidence: 99%
“…Pathogenicity of some transformants was assessed with a rice CO-39 cut leaf assay (Balhadère et al, 1999). Leaf segments were excised from the second leaf of a 14-d-old rice seedling.…”
Section: Pathogenicity Testmentioning
confidence: 99%
“…In recent years, many techniques have been developed to identify functional genes in M. grisea (Kamakura et al, 1999;Rauyaree et al, 2001;Takano et al, 2003;Irie et al, 2003;Lu et al, 2005). Of these techniques, insertional mutation method including REMI (restriction enzyme-mediated insertional mutagenesis) (Balhadère et al, 1999) and ATMT (Agrobacterium tumefaciens-mediated transformation) (Rho et al, 2001) is a powerful way for functional genomic analysis. This technique has been successfully used to transform diverse filamentous fungi and isolate important genes (Mullins and Kang, 2001) relying on screening a large number of transformants.…”
Section: Introductionmentioning
confidence: 99%